Comparative radiographic analysis of three-dimensional innate mobility of the foot bones under axial loading of humans and African great apes. Issue 11 (17th November 2021) - Negishi, Takuo; Ito, Kohta; Hosoda, Koh; Nagura, Takeo; Ota, Tomohiko; Imanishi, Nobuaki; Jinzaki, Masahiro; Oishi, Motoharu; Ogihara, Naomichi
Abstract : The human foot is considered to be morphologically adapted for habitual bipedal locomotion. However, how the mobility and mechanical interaction of the human foot with the ground under a weight-bearing condition differ from those of African great apes is not well understood. We compared three-dimensional (3D) bone kinematics of cadaver feet under axial loading of humans and African great apes using a biplanar X-ray fluoroscopy system. The calcaneus was everted and the talus and tibia were internally rotated in the human foot, but such coupling motion was much smaller in the feet of African great apes, possibly due to the difference in morphology of the foot bones and articular surfaces. This study also found that the changes in the length of the longitudinal arch were larger in the human foot than in the feet of chimpanzees and gorillas, indicating that the human foot is more deformable, possibly to allow storage and release of the elastic energy during locomotion. The coupling motion of the calcaneus and the tibia, and the larger capacity to be flattened due to axial loading observed in the human foot are possibly morphological adaptations for habitual bipedal locomotion that has evolved in the human lineage.